Focusing on Mechanoregulation Axis in Fibrosis: Sensing, Transduction and Effecting - Wen, Dongsheng; Gao, Ya; Ho, Chiakang; Yu, Li; Zhang, Yuguang; Lyu, Guozhong; Hu, Dahai; Li, Qingfeng; Zhang, Yifan (Frontiers in Molecular Biosciences, 2022)
Fibrosis, a pathologic process featured by the excessive deposition of connective tissue components, can affect virtually every organ and has no satisfactory therapy yet. Fibrotic diseases are often associated with organ dysfunction which leads to high morbidity and mortality. Biomechanical stmuli and the corresponding cellular response havebeen identified in fibrogenesis, as the fibrotic remodeling could be seen as the incapacity to reestablish mechanical homeostasis: along with extracellular matrix accumulating, the physical property became more “stiff” and could in turn induce fibrosis. In this review, we provide a comprehensive overview of mechanoregulation in fibrosis, from initialing cellular mechanosensing to intracellular mechanotransduction and processing, and ends up in mechanoeffecting. Our contents are not limited to the cellular mechanism, but further expand to the disorders involved and current clinical trials, providing an insight into the disease and hopefully inspiring new approaches for the treatment of tissue fibrosis.